Tissue-specific (ts)CRISPR as an efficient strategy for in vivo screening in Drosophila - Hagar Meltzer (Nature Portfolio, 2019)
Applicability of CRISPR-Cas9 for in vivo screening has so far been limited. Here the authors characterize tissue specific CRISPR in the Drosophila mushroom body, generating a library of gRNA-harboring plasmids and fly lines for in vivo screening.